ANALISIS VIKTIMOLOGIS TERHADAP KORBAN CATCALLING SEBAGAI BENTUK PELECEHAN SEKSUAL VERBAL - Murni, Luh Putu Lukat; Hariyanto, Diah Ratna Sari (Kertha Negara : Journal Ilmu Hukum, 2023)
Scientific paper is needed to be able to support legal research in connection with the development of legal science itself. The purpose of this article is to provide a deeper understanding and to critically examine the victim's point of view in dealing with victims of catcalling. In addition, this article will also examine further the existence of catcalling as a criminal act which is analyzed based on criminal law policies. To be able to answer the problems and achieve the right and appropriate writing objectives, this article uses normative methods by exploring the laws and regulations in Indonesia by approaching positive law and relevant criminal law concepts to solve problems. Victimology as one of the fields of legal science that is important to find the causes of the emergence of victims, is needed to analyze the causes of victims of catcalling. Whether the catcalling victim also played a role in causing the incident or not. However, because catcalling as a criminal act has not yet been specifically regulated in Indonesia, a written legal rule is needed in order to provide legal certainty for victims of catcalling. Keyword: Victimology, Catcalling, Criminal Act.